INFORMATION SYSTEM AND PRINCIPALS’ LEADERSHIP AT PUBLIC ELEMENTARY SCHOOLS IN PEKANBARU – RIAU - Hadriana; Isjoni; Mahdum; Azhar (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This descriptive research aims to analyze: (1) the availability and utilization of Information System at Public Elementary School in Pekanbaru - Riau and (2) principals’ leadership at Public Elementary School in Pekanbaru - Riau. By using proportional random sampling technique, 66 school principals spread across 12 sub-districts in Pekanbaru - Riau were selected as the sample. The instrument used was a questionnaire addressed to the principals. The principals are asked to give their answers to the given questionnaire and they were free to choose one or more answers for each item based their situation and condition. The data needed are related to the principals’ view of the availability and utilization of the Information System at the school they lead and the data about the principals’ view of leadership carried out related to the functions and roles they have done. The results of the data analysis prove that: (1) the availability of Information System at school was rated positively by the principals, whether in terms of availability, management, or perceived benefits; and (2) in carrying out leadership, their roles and functions as supervisors, managers and educators occupied the highest position.